The Effects of Selective Serotonin-Reuptake Inhibitor on Visual Evoked Potential in Rats - Yoshihiro Iwamura; Yoko Fujii; Chiaki Kamei (Elsevier, 2004)
The present study was undertaken to clarify the effects of selective serotonin-reuptake inhibitors (SSRIs) on visual evoked potential (VEP) in rats. To elucidate the mechanism of action of SSRIs, some serotonin (5-HT) agonists were used. SSRIs, fluvoxamine and paroxetine, caused a reduction in the amplitudes of P1-N1, P3-N3, and N3-P4 components of VEP. The amplitude of the P1-N1 component was also reduced by the 5-HT1A agonist 8-OH-DPAT and 5-HT1B agonist anpirtoline. On the other hand, amplitudes of P3-N3 and N3-P4 components were reduced by anpirtoline and the 5-HT2 agonist DOI. These results indicate that the reduction in the amplitude of the P1-N1 component of VEP induced by SSRIs may participate in 5-HT1A and 5-HT1B receptors, and those of P3-N3 and N3-P4 components induced by SSRIs may be closely related with 5-HT1B and 5-HT2 receptors. Keywords:: serotonin, fluvoxamine, paroxetine, visual evoked potential